Feeding common carp fish on diets containing different percentages of ginger (Zingbar officinale) and its effect on the characteristics of the blood and biochemical parameters - Al-Kurjia, Omar AbdulHameed (Journal of agricultural, environmental and veterinary sciences, 2023)
Common carp (Cyprinus carpio L.) were manually fed a diet supplemented with ginger powder (Zingiber officinalis) at levels (0, 6, 8, and 10) % to observe the effect of ginger powder on blood and biochemical parameters. The research was conducted in the fish laboratory of the Faculty of Animal Production /College of Agriculture and Forestry/University of Mosul. In this study 84 fish were used and distributed over 12 glass tanks with an average weight of 28 ± 1gm. The fish were fed 3 times a day at a rate of 3% of body weight for a period of 56 days. At the end of the experiment, there were significant differences (P
Keywords: Ginger; Common carp; biochemical parameters; blood standards